2022
DOI: 10.1186/s13722-022-00292-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ perspectives and perceived barriers to caring for patients with alcohol use disorder and cirrhosis

Abstract: Background Alcohol use disorder (AUD) is one of the leading etiologies for liver cirrhosis and liver transplantation. Few individuals with AUD receive guideline-based care in the form of screening, brief intervention, referral to treatment, or prescription of pharmacotherapy for relapse prevention. We interviewed clinicians across Alberta to assess the current experience and perceived barriers to managing AUD in people who have cirrhosis. The aim of this paper is to summarize these findings to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Complex and chronic diseases like ALD with cirrhosis and ascites require careful management, which can be exceptionally challenging for patients with unstable housing and healthcare access. Barriers to preventative care and chronic disease management services are common and difficult for many to overcome without assistance 3,14 . Close follow‐up is warranted, ideally from gastroenterology and primary care to prevent worsening progression of the disease and avoid complications 4,14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex and chronic diseases like ALD with cirrhosis and ascites require careful management, which can be exceptionally challenging for patients with unstable housing and healthcare access. Barriers to preventative care and chronic disease management services are common and difficult for many to overcome without assistance 3,14 . Close follow‐up is warranted, ideally from gastroenterology and primary care to prevent worsening progression of the disease and avoid complications 4,14 …”
Section: Discussionmentioning
confidence: 99%
“…Barriers to preventative care and chronic disease management services are common and difficult for many to overcome without assistance. 3 , 14 Close follow‐up is warranted, ideally from gastroenterology and primary care to prevent worsening progression of the disease and avoid complications. 4 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approved drug treatments for AUD are either contraindicated in cirrhosis (disulfiram, naltrexone and nalmefene) or lack an evidence base for safety, dosing and effectiveness (acamprosate, baclofen) 12–14 . These challenges create reluctance among prescribers and low uptake of treatments 15 . A retrospective study of 93,612 US veterans with cirrhosis found that only 1% had received behavioural and pharmacologic treatment for alcohol use disorder 16 …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These challenges create reluctance among prescribers and low uptake of treatments. 15 A retrospective study of 93,612 US veterans with cirrhosis found that only 1% had received behavioural and pharmacologic treatment for alcohol use disorder. 16 There are also treatments that may be of particular relevance to patients with established cirrhosis and might not be as effective in other populations.…”
Section: Introductionmentioning
confidence: 99%